Remote monitoring for heart failure management during COVID-19 pandemic. (February 2021) - Bertagnin, Enrico; Greco, Antonio; Bottaro, Giuseppe; Zappulla, Paolo; Romanazzi, Imma; Russo, Maria Daniela; Lo Presti, Marco; Valenti, Noemi; Sollano, Giuseppe; Calvi, Valeria
Graphical abstract: Abstract: Background: COVID-19 pandemic impacted on heart failure patients' lifestyle and quality of life, affecting both physical activity levels and state of health. Methods: Demographic data and device records were extracted for patients with heart failure in the 16 weeks at the turn of lockdown during pandemic. To explore the variability across the lockdown period, a week-to-week analysis was performed. Patients were interviewed to investigate physical activity and psychological insights. The primary endpoint was the variation in physical activity at the turn of lockdown. Results: At our facility, 2225 patients implanted with a cardiac device were screened and data were collected for 211 patients fulfilling the inclusion criteria. Patients' physical activity significantly decreased in the lockdown period compared with the control period (active time per day 8.0% vs. 10.8%; relative reduction [RRR] 25.9%; p < 0.0001). A small decrease was noted for mean heart rate (70.1 vs. 71.7 beats per minute [bpm]; RRR 2.2%; p < 0.0001), while thoracic impedance slightly increased (82.2 vs. 82.7 ohm; RRR 0.6%; p = 0.001). Patients' physical activity decreased from week 7 to week 11 (10.9% vs. 6.9%; RRR 36.7%; P < 0.0001) with an increase between week 11 and week 16 (6.9% vs. 8.5%; RRR 18.8%; P < 0.0001). Patients' perceptions about physical activity showed a very low correlation with remote monitoring-assessed physical activity levels (r 2  = 0.035, p = 0.039). Conclusions: Telemedicine and remote monitoring can explore the impact of COVID-19 pandemic on vital signs and physical activity levels of heart failure patients, playing a crucial role in the prediction of heart failure worsening during circumstances discouraging outpatient visits.